Thomas Hardy as dramatist - Gregory, R (2011)
This thesis traces Hardy's involvement in the theatre from the 1880s to the 1920s. The narrative of Hardy's relationship with the theatre is set against an analysis of the changing nature of the stage during this period, though I acknowledge throughout the thesis the fact that Hardy's awareness of the theatre did not perfectly keep pace with its evolution. The aim of the thesis is to examine the motivations determining Hardy's work in the theatre in light of the fact that he seemed so dismissive of its efficacy. I trace the history of Hardy's adaptations of his work for the stage, before setting the scripts against the novels in order to weigh the extent to which the novels resist translation into a different medium – whether there is something integral to Hardy's plots that cannot be conveyed on stage. I have chosen to focus predominantly on material that made it beyond a rough sketch on a scrap of paper, on projects that reached the stage of rewritings and commercial negotiations - often years before they were produced. My selection has been determined by the belief that the material is indicative of the development of Hardy's understanding of the relationship between his work and the possibilities adaptation offered. My first chapter, on the history of an adaptation of 'Far From the Madding Crowd' in 1882, argues that Hardy's collaboration with J. Comyns Carr on the script was driven by his desire to assert his copyright over the novel's afterlife. The adaptation may never have been performed, but simply have been registered with the Lord Chamberlain as a deterrent against unauthorised adapters. It was the plagiarism row over Arthur Wing Pinero's possible theft of Hardy's plot in his popular pastoral play, 'The Squire', that pushed Hardy and Carr to stage their version. My second chapter looks at the history of Hardy's adaptations of 'Tess'. I am interested primarily in his writing of two scripts in the mid-1890s, and his negotiations with leading actresses in response to their interest in creating the part of Tess. The chapter then looks at the circumstances leading to the eventual staging of the play in the 1920s, focusing on the difficulties posed by producing a script which was by then thirty years old, and showing its age. In the third chapter I concentrate on plans to stage two novels, 'The Woodlanders' and 'Jude'. Neither was produced, but both are evidence of Hardy's increasing interest in the possibility of selecting from his material, rather than compressing it into the time available. The two adaptations allied Hardy much more closely with the avant garde than his earlier work had done – 'The Woodlanders' was begun in 1889 at the suggestion of J. T. Grein and C. W. Jarvis, two men who would later found the Independent Theatre, a private subscription society which pioneered the staging of Ibsen in England. Hardy's own sketches for adapting 'Jude' (1895, 1897, 1910, 1926) concentrated on Sue's position. I set Hardy’s realignment of 'Jude' against a focus on the place of women in unhappy marriages, drawing principally on Hardy's contribution to a debate about the role of wives in the 'New Review' for June 1894 and a 'Westminster Review' article by the feminist Mona Caird (August 1888), which provoked three months of debate (and 27,000 letters) in 'The Daily Telegraph' on the question 'Is Marriage a Failure?' Caird’s ideal dovetails with Sue's views on marriage as 'legalized prostitution' and her revulsion from 'the dreadful contract to feel in a particular way in a matter whose essence is its voluntariness!' The final chapter of the thesis looks at two adaptations of 'The Dynasts'. The first is a wartime entertainment staged by Harley Granville Barker in 1914, the second is Hardy's own adaptation for Dorset amateur actors (the Hardy Players) to perform in 1916, which concentrated on the impact of the war on the local populace. I then turn to the premiere of Hardy's only full-length drama written specifically for the stage – the one-act Arthurian play 'The Queen of Cornwall' (1923). I argue in this final chapter that Hardy was beginning to move from the role of reluctant adapter to that of director, conscious of the boundaries imposed by the stage and experimenting with how to craft his work to fit within them, rather than abridging his material indiscriminately.